2018
DOI: 10.1111/hsc.12537
|View full text |Cite
|
Sign up to set email alerts
|

Implementing health and social care integration in Scotland: Renegotiating new partnerships in changing cultures of care

Abstract: Health and social care integration has been a long-term goal for successive governments in Scotland, culminating in the implementation of the recent Public Bodies (Joint Working) Scotland Act 2014. This laid down the foundations for the delegation of health and social care functions and resources to newly formed Integrated Joint Boards. It put in place demands for new ways of working and partnership planning. In this article, we explore the early implementation of this Act and how health and social care profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 26 publications
1
64
0
2
Order By: Relevance
“…In this context, senior medical professionals in the acute sector are increasingly required to accommodate, re-interpret and integrate market, corporate and state logics into their professional identities and relationships with other clinical and care professionals (Pearson & Watson, 2018).…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…In this context, senior medical professionals in the acute sector are increasingly required to accommodate, re-interpret and integrate market, corporate and state logics into their professional identities and relationships with other clinical and care professionals (Pearson & Watson, 2018).…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…Our data suggest that the attitude of non-cooperation between social and health care providers, and a lack of systematic approaches for e cient collaboration (e.g., uncertainties about professional roles and functions, lack of mutual formal communication pathways) hamper provisions of integrated care for patients with complex needs. Previous research indicates that a policy shift toward integration is not an easily achievable task, as individual innovators, and not legal imperatives are often the key drivers of change [8]. A study assessing the different types of collaborative ties between healthcare and social care services organizations concluded that co-sponsoring projects could be listed among the most effective ways of fostering effective partnerships [13].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that patients with complex LTC needs experience multiple parallel care processes, which may have con icting or competing goals within their individual patient trajectories [7]. Thus, the reorganization of social and health care processes focusing on dementia patients has become one of the top priorities across countries, and a large array of tools, including attitudinal, organizational, and regulatory transformation of care delivery, have been applied with the aim to foster integrated service delivery [3,[7][8][9][10]. Studies indicate that a partnership between health care and social services results in higher user satisfaction with the care received [11,12], and lower avoidable health care use and spending [13].…”
Section: Introductionmentioning
confidence: 99%
“…Myös arviointitietoa toimeenpanon sujumisesta ja tuloksista oli niukasti vielä saatavilla. Pearson & Watson (2017) tunnistivat Skotlannin sosiaali-ja terveydenhuollon integraatiota koskevassa tutkimuksessaan alkuvaiheen kokemuksia integraation toimeenpanosta. Heidän huomionsa mukaan integraation rakentaminen on jätetty yksittäisille toimijoille.…”
Section: Integraatio Kansainvälisessä Sote-palvelujärjestelmässäunclassified